An Investigation into Factors Affecting UK Influence UK Female Ethical Consumers Purchase Behaviours on Green Beauty and Health Products - qiu, ximin (2019)
In recent years, consumers are placing more importance on environmental and social outcomes of their purchase choices. They are increasingly realizing that they can use their customer sovereignty to prompt companies to address social and environmental issues more enthusiastically. This explains the increasingly high demand for green products in the market. Meanwhile, more and more companies have started to position themselves as green to respond to this demand. However, with the explosion of green products and green marketing in the market, customers feel it hard to assess the credibility of the information given by companies and they have begun to lose their trust in all green ads due to the greenwashing practices of some companies. Therefore, it is imperative for companies to have a better understanding of the formation of their purchase behaviour and make effective strategies to help customer rebuild trust. Existing studies on consumers’ attitudes and purchase behaviours of green products mainly focus on organic food products, green technology products or general green products. As green beauty and health industry has started to grow, little researches have been done to explore the green purchase intentions on personal care products business. Therefore, this research aims to fill this gap to explore the factors that influence consumer purchase intentions toward green personal care products and the results of this study can not only provide companies with valuable implications for marketing but also extend the literature on green purchase behaviour. Data were collected from 15 female ethical consumers in the UK through face-to-face semi-depth interviews on recent purchases of green beauty and health products. The results reveal that attitude, subjective norms, and perceived behavioural control are three dimensions that determine ethical consumer green purchase intentions. In addition, customer attitude toward green beauty products is influenced by health consciousness and environmental consciousness of customers. Three green product attributes include green claims, eco-labels and ingredient labels have effects on their attitude. Results indicate that family and friends and online interpersonal influence. Drivers and barriers to customer green purchase behaviour are identified in this study. Constraints include perceived higher price by price-sensitive customers, limited product availability and options, extra time for researching and shopping, lack of knowledge about the meaning of the standard of the green products and the benefits of products. Green corporate image and service reduce customers’ cognitive efforts and make them feel easy to purchase green beauty and health products. Based on these findings, a model of green purchasing behaviour towards green personal care products is developed. This study suggests that manufacturers need to embed sustainability into the entire value chain, especially the use of organic ingredients, minimal waste packaging and eco-friendly shipping process. Marketers also need to develop effective marketing strategies which link the above three aspects with their health and environmental benefits. Marketers also need to make sure that the green claims are backed up by recognizable independent third party eco-labels. Meanwhile, they should educate customers the knowledge of these eco-labels to increase their awareness and trust in these eco-labels. Besides, marketers should motivate online interactions between customers on all channels, including social media platform, official or partner websites. Moreover, they can foster their green images by demonstrating the achievement of the sustainable or not-for-profits projects they engage. For policymakers, they should make policies and legislation on companies’ green marketing messages to effectively reduce greenwashing practices. Moreover, they should make consistent recycling systems and infrastructure across the UK to make it easy for customers to recycle.